Entre muros invisíveis: as sociabilidades de jovens na experiência do acolhimento institucional em Sapucaia do Sul-RS - Pacheco, Patrícia Brum (Universidade do Vale do Rio dos Sinos, 2018)
This dissertation is the result of a research about the forms of sociability of young people in the experience of institutional reception in Sapucaia do Sul, seeking to understand the benefits of expanding social circles. Therefore, the concept of sociabilities from the work of Georg Simmel is central to sociological analysis, understanding that sociability and identities are relational processes. The methodology used is based on ethnography from the symbolic interactionism, which sought for the participant observation, interviews and documentary survey contents to the parsing of the meanings attributed by the young people received on their social interactions inside and outside the shelter. Thus, field research was fundamental to unveil the structuring concepts of forms of sociability, conflict and violence being the main language adopted by young people, a consequence of social stigma and non-recognition as content that permeates social interactions. Considering the relevance of the context of this research, the Shelter, the dualisms of the institutional reception service were verified. Conflicting sociabilities, therefore, are constrained in the between spaces that Shelter occupies in the lives of young people, where new forms of social interactions are metaphorically blocked by visible and invisible walls. Visible walls isolate young people from the world of the street, while invisible walls restrict the formation of social networks through the expansion of social circles, that is, of real and virtual social networks, essential for the re-signification of experiences of conflict and violence that structure their forms of sociability.
Keywords: Sociabilidades; Identidades; Acolhimento Institucional; Jovens; Conflito; Sociability; Identity; Institutional reception; Young; Conflict; ACCNPQ::Ciências Humanas::Sociologia